Polyphyllin VI, a saponin from Trillium tschonoskii Maxim. induces apoptotic and autophagic cell death via the ROS triggered mTOR signaling pathway in non-small cell lung cancer. (September 2019) - Teng, Jin-Feng; Qin, Da-Lian; Mei, Qi-Bing; Qiu, Wen-Qiao; Pan, Rong; Xiong, Rui; Zhao, Ya; Law, Betty Yuen-Kwan; Wong, Vincent Kam-Wai; Tang, Yong; Yu, Chong-Lin; Zhang, Feng; et al.
Graphical abstract: Abstract: Non-small cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancers. Our previous studies have proven that Trillium tschonoskii Maxim. (TTM), a traditional Chinese medicine, possesses potent anti-tumor effect. However, the detailed components and molecular mechanism of TTM in anti-NSCLC are still unknown. In the present experiment, polyphyllin VI (PPVI) was successfully isolated from TTM with guidance of the anti-proliferative effect in A549 cells, and the cell death of PPVI treated A549 and H1299 cells was closely linked with the increased intracellular ROS levels. In addition, PPVI induced apoptosis by promoting the protein expression of Bax/Bcl2, caspase-3 and caspase-9, and activated autophagy by improving LC3 II conversion and GFP-LC3 puncta formation in A549 and H1299 cells. The mechanism study found that the activity of mTOR which regulates cell growth, proliferation and autophagy was significantly suppressed by PPVI. Accordingly, the PI3K/AKT and MEK/ERK pathways positively regulating mTOR were inhibited, and AMPK negatively regulating mTOR was activated. In addition, the downstream of mTOR, ULK1 at Ser 757 which downregulates autophagy was inhibited by PPVI. The apoptotic cell death induced by PPVI was confirmed, and it was significantly suppressed by the overexpression of AKT, ERK and mTOR, and the induced autophagic cell death which was depended on the Atg7 was decreased by the inhibitors, such as LY294002 (LY), Bafilomycin A1 (Baf), Compound C (CC) and SBI-0206965 (SBI). Furthermore, the mTOR signaling pathway was regulated by the increased ROS as the initial signal in A549 and H1299 cells. Finally, the anti-tumor growth activity of PPVI in vivo was validated in A549 bearing athymic nude mice. Taken together, our data have firstly demonstrated that PPVI is the main component in TTM that exerts the anti-proliferative effect by inducing apoptotic and autophagic cell death in NSCLC via the ROS-triggered mTOR signaling pathway, and PPVI may be a promising candidate for the treatment of NSCLC in future.